The seducer's diary - 1813-1855.; Hong, Howard V. (Howard Vincent), 1912-2010.; Hong, Edna H. (Edna Hatlestad), 1913-2007. (Princeton, N.J. : Princeton University Press, 1997)
"This work, a chapter from Kierkegaard's first major volume, Either/Or, springs from his relationship with his fiancee, Regine Olsen. Kierkegaard fell in love with the young woman, ten years his junior, proposed to her, but then broke off their engagement a year later. This event affected Kierkegaard profoundly. Olsen became a muse for him, and a flood of volumes resulted. His attempt to set right, in writing, what he feels was a mistake in his relationship with Olsen taught him the secret of "indirect communication." The Seducer's Diary, then, becomes Kierkegaard's attempt to portray himself as a scoundrel and thus make their break easier for her." "Matters of marriage, the ethical versus the aesthetic, dread, and, increasingly, the severities of Christianity are pondered by Kierkegaard in this intense work."--BOOK JACKET.
Includes bibliographical references (pages 201-214).
Keywords: Self (Philosophy); Self (Philosophy)